Examining the Evolution of Technological Conditions from the Point of View of the Application of Blockchain-based Data Management in Food Supply Chains - András Bertalan; Balazs Gyenge; Károly Kacz (Chemical Engineering Transactions, 2023)
A critical point in making food chains more sustainable is to find different ways to increase efficiency. These can be aimed at shortening the chain, using more sustainable raw materials, etc. Blockchain technology offers the potential for reliable data management and simplified administration and is, therefore, definitely a tool to consider if the aim is to enhance sustainability in food chains. The question arises as to whether food chain operators have the technology and knowledge needed for widespread uptake. The aim of this research was to investigate whether the technical background and knowledge for the use of cryptocurrencies can be compared with the technological background for monitoring the food chain with blockchain-based data management. If so, since data on the uptake of cryptocurrencies is already available, this analysis will provide information on the realistic scope of such an application. The research showed that there is no significant difference in the technology required for the two applications. The data clearly shows that, overall, there are 4.6 billion people who have the tools to use them. In addition, there is evidence that cryptocurrency penetration is weakly correlated with GDP or banking system development. In other words, if other conditions are right (e.g., the interest of producers), the availability of tools and knowledge should not be a barrier to uptake. Neither is the economic performance of a country or the development of its banking system. It is therefore concluded that, based on the aspects examined in this research, blockchain technology can be applied on a large scale worldwide.